Effect of dietary energy concentration on performance parameters and egg quality of white leghorn laying hens - Ribeiro,PAP (2014)
An experiment was carried out with 1200 23-week-old white Dekalb commercial laying hens to investigate production responses, egg quality, and energy utilization of laying hens fed different dietary energy levels at the beginning of lay. Birds were housed and divided in five groups of 240 birds according to dietary apparent metabolizable energy corrected for nitrogen (AMEn): 2700 kcal/kg; 2775 kcal/kg; 2850 kcal/kg; 2925 kcal/kg; and 3000 kcal/kg, with six replicates of 40 birds each. Birds were fed the experimental diets based on corn and soybean meal for 17 weeks. Diets were iso-nutritive, except for energy level. Increasing AMEn levels had a negative effect on egg production and egg mass (p≤0.05). AMEn levels did not influence body weight, egg weight, or livability (p>0.05). Increasing AMEn levels increased (p≤0.05) feed intake and AMEn conversion ratio and feed conversion ratio. AMEn intake remained constant, independently of dietary AMEn level (p>0.05). There were no differences in albumen height, yolk total solids content, or egg component percentages (p>0.05). Egg specific weight improved with increasing AMEn levels (p≤0.05). Therefore, the energy level of 2700 kcal/kg of feed may be fed to young laying hens.